2011
DOI: 10.1093/nar/gkr371
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Mcm2 modulates Mcm2–7 activity and affects the cell’s response to DNA damage

Abstract: The S-phase kinase, DDK controls DNA replication through phosphorylation of the replicative helicase, Mcm2–7. We show that phosphorylation of Mcm2 at S164 and S170 is not essential for viability. However, the relevance of Mcm2 phosphorylation is demonstrated by the sensitivity of a strain containing alanine at these positions (mcm2AA) to methyl methanesulfonate (MMS) and caffeine. Consistent with a role for Mcm2 phosphorylation in response to DNA damage, the mcm2AA strain accumulates more RPA foci than wild ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 71 publications
(104 reference statements)
2
43
0
Order By: Relevance
“…suppresser mutations (26,27). Thus, these previous, native promoter experiments should be interpreted with caution.…”
Section: Dbf4-cdc7 Phosphorylates Mcm2 During S Phase Under Normal Grmentioning
confidence: 92%
See 4 more Smart Citations
“…suppresser mutations (26,27). Thus, these previous, native promoter experiments should be interpreted with caution.…”
Section: Dbf4-cdc7 Phosphorylates Mcm2 During S Phase Under Normal Grmentioning
confidence: 92%
“…Dbf4-Cdc7 phosphorylates Mcm2 in vitro (24,25), but the physiologic role of Dbf4-Cdc7 phosphorylation of Mcm2 is unclear. It has been shown that in vitro, Dbf4-Cdc7 phosphorylates Mcm2 at serines 164 and 170 (25,26). When the gene for mcm2-S164A-S170A (mcm2-2A) is expressed from its endogenous promoter on a plasmid and the cells harboring this plasmid are subjected to a plasmid shuffle assay, no growth defect is observed (26).…”
mentioning
confidence: 99%
See 3 more Smart Citations